Line Spread Test Results for Commercially Available the White Rice Porridge with Sticky Barley (Global Journal of Medical Research, 2023)
In the event of a disaster, we will have to take stockpiled food. Retort porridge contains water and can be eaten directly from the container. However, there is a risk of aspiration for people with impaired swallowing function. As a result of the line spread test (LST), which was performed after homogenizing white rice porridge with sticky barley using a mixer, it was found that the viscosity was weak, and there was a risk of aspiration for people with weakened swallowing function. The thickness was added to white rice porridge with sticky barley by using four types of commercially available thickening agents that was made into a uniform liquid with a mixer. A line spread test (LST) was performed by adding 2 g of each thickening agent to 100g of liquid porridge. As a result, the viscosity of the liquid porridge was stabilized and thickened, and it became a state that could swallow more safely. In the line spread test, the thickness of the porridge was measured after 30 seconds, 5 minutes, 15 minutes, and 30 minutes.
Keywords: commercial product; white rice porridge with sticky barley; lin spread test (LST); thickener